Comparison of amniotic membrane transplantation with and without cultured limbal epithelium for persistent corneal ulcers. Issue 1 (1st January 2021) - Hristova, Rozaliya; Zdravkov, Yani; Markov, Georgi; Borroni, Davide; Oscar, Alexander; Petkova, Iva
Abstract: This study compared the clinical outcomes of amniotic membrane transplantation with and without cultured limbal epithelium for persistent corneal ulcers. The study included 30 patients that were assigned to either human amniotic membrane transplantation (AMT) only or a two-step cultured limbal epithelial transplant (CLET) with amniotic membrane carrier. The patients underwent a comprehensive ocular examination, Cochet-Bonnet esthesiometry, impression cytology and anterior segment optical coherence tomography (AS-OCT). Slit-lamp images before and after treatment were analyzed using ImageJ to compare the fibrovascular tissue area. The state of epithelialization was assessed by fluorescein staining on day 30. Mean age of patients was 64 ± 20.39 in the AMT group and 55.17 ± 14.51 in the CLET group ( p  = 0.16). Visual acuity improved significantly in both groups after treatment, but the improvement was significantly greater in the CLET group ( p  = 0.022). Impression cytology demonstrated PAS + cells in the corneal epithelium in 9 patients from the CLET group and 10 patients in the AMT group ( p  = 0.704). Cochet-Bonnet esthesiometry increased significantly after treatment with a similar rate between groups ( p  = 0.435). Improvement with reduction of the fibrovascular tissue area was achieved in both groups ( p  < 0.01 and p  = 0.001 in the CLET and AMT group, respectively). Independent samples T -test demonstrated a greater reduction in the CLET group ( p  = 0.028). Kaplan-Meier analysis of epithelialization demonstrated higher success rate in the CLET group ( p  = 0.006). Persistent corneal ulcers could be associated with partial limbal stem cell deficiency (LSCD). In refractory cases, CLET should be the preferred treatment option with more sustainable results regarding corneal epithelialization and stromal scarring.